Applicability of the Pull-Off Test: Teachings from a large sample of in situ tests - N. M. M. Ramos (2011)
The Pull-off test is a very popular way of evaluating the adhesion strength of renderings or ceramic revetments. Several standards frame the application of this test and its results interpretation. The Laboratory of Building Physics (LFC-FEUP) has used the pull-off test results in several cases to support the diagnosis of causes for building anomalies. In this article, 56 case studies based on in situ tests are analysed. The sample was retrieved from 16 test reports conducted by LFC-FEUP. In each of these reports different situations were analysed in terms of wall components, expected hygrothermal loads, and in testing procedures followed. This large number of tests support a discussion on two subjects: the applicability of the pull-off test and the parameters that can influence the results observed in this sample. The first subject, the applicability of the pull-off test, was observed for different systems, including ceramic tiles applied with cement based adhesives, cement based renderings and ETICS. Difficulties and opportunities of the test are analysed for each material. In the second subject, the variability observed in each case study was used in different correlations revealing patterns that can be expected when applying this test. These results support a discussion on uncertainty appraisal of the pull-off test.